2017
DOI: 10.1111/cdev.12749
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Implicit Memory From Infancy to Childhood: On Average Performance Levels and Interindividual Differences

Abstract: The present multimethod longitudinal study aimed at investigating development and stability of implicit memory during infancy and early childhood. A total of 134 children were followed longitudinally from 3 months to 3 years of life assessing different age-appropriate measures of implicit memory. Results from structural equation modeling give further evidence that implicit memory is stable from 9 months of life on, with earlier performance predicting later performance. Second, it was found that implicit memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The authors believe that unconscious social interaction and unconscious thinking are related, taking together the above-mentioned findings and assumptions from other concepts of the review (from chapters 1-3), and due to the opinion that 'implicit memory is present from early on', as well as another one that the capacity for behavioral imitation, and the properties of the mirror neuron system, are constructed in the course of development through associative learning [18,20]. Putting all these arguments together, it can also be assumed that people in society are unconsciously connected all their lives and such cooperation affects cognition, and the unconscious domain of thinking participates in this unconscious social exchange.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The authors believe that unconscious social interaction and unconscious thinking are related, taking together the above-mentioned findings and assumptions from other concepts of the review (from chapters 1-3), and due to the opinion that 'implicit memory is present from early on', as well as another one that the capacity for behavioral imitation, and the properties of the mirror neuron system, are constructed in the course of development through associative learning [18,20]. Putting all these arguments together, it can also be assumed that people in society are unconsciously connected all their lives and such cooperation affects cognition, and the unconscious domain of thinking participates in this unconscious social exchange.…”
Section: Discussionmentioning
confidence: 84%
“…Results from structural equation modeling give further evidence that implicit memory is stable from 9 months of life onwards, with earlier performance predicting later performance. Second, it was found that implicit memory is present from early age onwards, and no age-related improvements are found from 3 months onwards [18].…”
Section: Review Of the Studies Based On The Concepts Of Unconscious Tmentioning
confidence: 93%
“…That is, prior information, which here was built up from trial to trial, may be less available to infants and children compared to adults. Prior studies offer contradictory evidence as to whether there are significant changes in the structure and mechanisms of early memory (Nelson, 1995;Rovee-Collier, 1997;Rovee-Collier et al, 1999;Vöhringer et al, 2018), but there is consensus that infants can build knowledge across sequentially presented stimuli (e.g., Lew-Williams & Saffran, 2012;Maye et al, 2002;Thiessen & Saffran, 2007) and that the ability to retain information over longer periods improves with age and experience (Beckner et al, 2020;Gathercole et al, 2004;Simmering, 2016). It could be that younger learners retain weaker representations of previouslyexperienced exemplars, such that early events have reduced influence on their perception.…”
Section: Discussionmentioning
confidence: 99%
“…The basic assumption was that infants would learn the sequence of the stimulus presentation across trials and accelerate the direction of their gaze with anticipatory reactions with each successive trial. In fact, Vöhringer et al () confirmed this assumption but also showed that performance on the VexP index of implicit memory did not change significantly during the first year of life, even though individual stability over this time period was rather low.…”
Section: New Developments In the Fieldmentioning
confidence: 92%
“…Because priming tasks cannot be used with infants, researchers have employed a visual expectation (VexP) procedure to assess developmental changes in implicit memory in preverbal children. For instance, on each trial of this task, Vöhringer et al () presented smiling female faces in succession at different positions of a computer screen for a second, with each face followed by a blank 1.5 seconds interstimulus interval. The infants' gaze movements were recorded via video and analysed frame by frame for each trial.…”
Section: New Developments In the Fieldmentioning
confidence: 99%